Conjunctive Use of Rain and Groundwater in Pearl Millet - Singh, S D; Mathur, B K (Annals of Arid Zone, 2016)
Unless affected by a severe drought similar to that of 1987 and 002, crops in arid Rajasthan usually fail for want of 20 to 25 mm of rain, especially a the fag end of the season. This happened in 2005 cropping season. As there are fertile lCkets (oasis), due to the presence of water, scattered over the region, crop failure can e averted by way of groundwater supplementation to precipitation. In 1996, for instanc , pearl millet yield was 1725 kg ha-1 from rain alone, and when supplemented with 68, 179 and 204 mm of groundwater, crop yields improved to 2466, 3424 and 3615 kg ha- , respectively. Data for the 1998 season further revealed the significance of rain-groundwat~r conjunctive use. Combining suboptimal Crop Water Supply (CWS:256 mm rain + 60 mn} groundwater = 316 mm) with optimal fertilizer use (60 kg ha-1 N) brought about 2755 kgl ha-1 of grain. "Bare economic optimum" CWS (353 mm) combined with 90 kg ha-1 N te~ded to move the pearl millet yield curve up to 3010 k? ha-1 . A CWS equal to "physiologtcal optimum" (450 mm) in combination with 120 kg ha- N, envisaged for hi-tech pearl millet production system, resulted in "top profitable yield" at 3750 kg ha-1 . Such yield ensur~' the best use of natural resources as well as external inputs, besides assured food security. To this CWS, 194 mm was supplemented from groundwater. If it were to be used in t rabi season, no winter crop is expected to yield even the "minimum acceptable yield in pr fitable range". Hence, the use of groundwater in water-responsive pearl millet seems a payin~ undertaking. As supplement is feasible only by sprinkler system, sprinkler-set renting station in each oasis merits consideration by the state government in order for distribution OfrOCialbenefits to as many farmers as feasible. Policy-makers are to weigh the feasibility f sprinkler-set renting stations.. Key words: Rainwater, groundwater, nitrogen level, pearl millet, root grol tho